Towards Sustainable and Resilient Tourism Futures Insights from the International Competence Network of Tourism Research and Education (ICNT) - Köchling, Anne; Seeler, Sabrina; Merwe, Peet; Postma, Albert (Schriftenreihe des Deutschen Instituts für Tourismusforschung,, 2023)
This book is open access. "The competitiveness of tourism products and tourist destinations heavily relies on natural and social resources. At the same time, the tourism industry's environmental footprint and its contribution to social inequalities are incontestable. A transformation towards more sustainable tourism futures is needed to ensure a positive contribution to fulfilling the UN's Sustainable Development Goals. Today's challenges, desirable pathways and solutions are portrayed in this book, which was co-authored by members of the International Competence Network of Tourism Research and Education (ICNT). In 12 chapters, the scholars from diverse cultural backgrounds discuss - aspects of sustainable and resilient tourism futures with reference to the attitude and behaviour of selected tourist groups, - management of wildlife protection and of sustainability aspects by industry stakeholders as well as - strategies to overcome COVID-19 induced issues. The different chapters take the reader on a journey around the globe while discussing sustainability along the triple bottom line." This is an open access book.